THE STUDY OF USEFULNESS OF DISPERSIBLE BITUMINOUS MATERIALS FOR PLUGGING HIGH-CONDUCTIVITY CRACKS IN OIL ACCUMULATION - Бойко, Василь Степанович; Заливаха, Назарій Ярославович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
According to the data published characteristics and the results of laboratory researches the correspondence of ground softening agent, structure-forming agent and rubrax to requirements to the guided dispersible systems has been ascertained. These systems are useful for plugging high-conductivity cracks in oil accumulation.